Case report: Use of penicillin G potassium in poloxamer 407 gel to aid in healing of an equine sublingual abscess - Larsen, Elizabeth A.; Lack, Amy C.; Wassack, Erica (Frontiers in Veterinary Science, 2022)
The use of poloxamer 407 gels have been reported in several studies to prolong the release of drugs at the injection site. Oral lesions unrelated to dental disease are rare but may result in ulceration and sequestration of bone. To date, there have been no reports on the use of penicillin G potassium poloxamer 407 gel and its effect on wound healing. The present case report describes the use of a penicillin G potassium poloxamer 407 gel for the treatment of a sublingual abscess involving the mandible in a 20 year old Arabian mare who initially presented with acute onset of dysphagia, hypersalivation, and a mass under the tongue. A presumptive diagnosis of lingual cellulitis was made, and a sublingual abscess ruptured on day 7 of hospitalization. In this case, poloxamer 407 gel was used to decrease wound contamination, protect the exposed mandible, and potentially prolong the release of penicillin G potassium into the wound.